THE CHEMICAL ANALYSIS OF GALL STONES IN THE SOUTHEAST TURKEY - Halil DEĞERTEKİN,; Özden UZUNALİMOĞLU,; Bülent ALIÇ,; Samet AKBABA,; Vedat GÖRAL,; Güler GÖYMEN,; Meral HOŞCAN, (Turkish Journal of Gastroenterology, 2020)
-